Quality Cookies Kastengel Cornstarch Substitution - Azizah, Nurul; Holinesti, Rahmi; Gusnita, Wiwik; Indrayeni, Wiwik (Universitas Negeri Padang, 2024)
This research aims to analyze the effect of corn flour substitution of 20%, 40%, and 60% on the quality of shape, color, aroma, texture and taste of Kastengel cookies This research aims to analyze the effect of corn flour substitution of 20%, 40% and 60% on the quality of shape, color, aroma, texture and taste of Kastengel cookies. This type of research is experimental using quantitative methods with organoleptic test format for the quality of Kastengel cookies with corn flour substitution. The data obtained was then tabulated in table form and analyzed using analysis of variance (ANAVA), If Fcoun > Ftable, it was continued with the Duncan test. The results of this research show that there is a significant effect of corn flour substitution of 20%, 40% and 60% which is significant for the quality of color, texture and taste, while for the quality of shape and aroma it has no effect. The results of data analysis obtained the highest overall achievement score, namely rectangular shape quality 4.00 (rectangle), uniform shape quality 3,78 (fairly uniform), neat shape quality 4.00 (uniform). Color quality 3,89 (quality yellow), aroma quality 3,78 (quality cheese-flavored), crumbly texture 3,67 (quite brittle), savory taste 3,89 (quite savory) and corn taste 2.78 (lacking taste corn). The results of the best quality test for kastengel cookies with corn flourr substitution were in treatment X3 with 60% corn flour substitution.